Broad temperature range of cubic blue phase present in simple binary mixture systems containing rodlike Schiff base mesogens with tolane moiety. Issue 12 (24th February 2016) - Huang, Chiung-Cheng; Chen, Yu-Hao; Chen, Sheng-Yen; Sun, Yi-Zeng; Wu, Zong-Ye; Yu, Mei-Ching; Chen, Bo-Hao; Hsu, I-Jui; Wu, Lai-Chin; Lee, Jey-Jau
Abstract : The widest temperature range of the cubic BP (∼35 °C) can be induced by adding a rodlike chiral dopant, R811 orS811, into the rodlike racemic Schiff base mesogen with hydroxyl group. On the basis of our experimental results and molecular modeling, we demonstrated that the hydroxyl group in this type of Schiff base mesogen plays an important role in the stabilization of BPs. Abstract : Four simple rodlike Schiff base mesogens with tolane moiety were synthesized and applied to stabilize cubic blue phases (BPs) in simple binary mixture systems for the first time. When the chiral additiveISO(6OBA)2 orR811 was added into a chiral salicylaldimine-based compound, the temperature range of the cubic BP could be extended by more than 20 °C. However, when the chiral Schiff base mesogen was blended with chiral dopant possessing opposite handedness, S811, BPs could not be observed. Interestingly, the widest temperature range of the cubic BPs (∼35 °C) could be induced by adding the rodlike chiral dopantR811 orS811 into the rodlike racemic Schiff base mesogen with hydroxyl group. On the basis of our experimental results and molecular modeling, the appearance and temperature range of the BPs are affected by the dipole moment and the biaxiality of the molecular geometry. Accordingly, we demonstrated that the hydroxyl group and the methyl branch in this type of Schiff base mesogen play an important role in the stabilization of BPs.